2012
DOI: 10.1109/jssc.2011.2179451
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of a Hardware-Efficient Compressed Sensing Architecture for Data Compression in Wireless Sensors

Abstract: Abstract-This work introduces the use of compressed sensing (CS) algorithms for data compression in wireless sensors to address the energy and telemetry bandwidth constraints common to wireless sensor nodes. Circuit models of both analog and digital implementations of the CS system are presented that enable analysis of the power/performance costs associated with the design space for any potential CS application, including analog-to-information converters (AIC). Results of the analysis show that a digital imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
229
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(232 citation statements)
references
References 35 publications
2
229
0
1
Order By: Relevance
“…The numerical results show that structured sampling, in combination with structured recovery, allows to more faithfully reconstruct the original signals, as compared with the traditional Bernoulli [4] or the multi-channel sampling [5] schemes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The numerical results show that structured sampling, in combination with structured recovery, allows to more faithfully reconstruct the original signals, as compared with the traditional Bernoulli [4] or the multi-channel sampling [5] schemes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the MCS strategy has been designed to optimize area and power usage, at the cost of sacrificing the reconstruction quality when the channels are not correlated enough. The random Bernoulli sampling [4] offers excellent reconstruction quality at low compression factors, but requires a larger chip area than MCS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in spite of the immaturity of the field, it has been shown that energy efficiency, circuit size, and power consumption of a CS encoder are on par with or better than the state-of-the-art of existing compression methods [7][8][9][10][11][12][13][14][15][16].…”
Section: Journal Of Neurology and Neuroscience Issn 2171-6625mentioning
confidence: 99%
“…The most striking waveform when considering the ECG is QRS wave complex, which gives the R wave peak which is time-varying [6]. Wavelet transform (WT) is a powerful time-frequency signal analysis tool and it is used in a wide variety of applications [7]. The question is how to use the Wavelet Transform for the purpose of getting rid of Baseline Wander ECG signal?…”
Section: Introductionmentioning
confidence: 99%